Inter-disciplinarity in sport sciences: The neuroscience example*. Issue 1 (2nd January 2017) - Fargier, Patrick; Collet, Christian; Moran, Aidan; Massarelli, Raphaël
Abstract: Sport science is a relatively recent domain of research born from the interactions of different disciplines related to sport. According to the European College of sport science (http://sport-science.org ): "scientific excellence in sport science is based on disciplinary competence embedded in the understanding that its essence lies in its multi- and interdisciplinary character". In this respect, the scientific domain of neuroscience has been developed within such a framework. Influenced by the apparent homogeneity of this scientific domain, the present paper reviews three important research topics in sport from a neuroscientific perspective. These topics concern the relationship between mind and motor action, the effects of cognition on motor performance, and the study of certain mental states (such as the "flow" effect, see below) and motor control issues to understand, for example, the neural substrates of the vertical squat jump. Based on the few extensive examples shown in this review, we argue that by adopting an interdisciplinary paradigm, sport science can emulate neuroscience in becoming a mono-discipline.